Peste des petits ruminants in Northern Sudan. - Saeed, Intisar Kamil; Ali, Yahia Hassan; Abdellatif, Muaz Magzob; Ataalfadeel, Husham Mohammed; Alsharari, Anwar A; Abdel-Mageed, Ahmed Mohammed; Abu-Tahon, Medhat Ahmed; Rikabi, Hind Abdelmajeed; Mustafa, Alaa Ahmed (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This work is to elucidate the prevalence of Peste des Petits (PPR) in Northern Sudan through antibody, antigen, and genome detection. Materials and Methods: Serum and tissue samples from lungs showing pneumonic lesions of goats and sheep were collected in slaughterhouses in both states in Northern Sudan. Sera were examined for antibodies to the PPR virus by Competitive ELISA; Immunocapture ELISA was used for testing PPRV antigen in lung tissues. Some of the ELISA-positive tissues were examined for the PPRV genome by reverse transcription PCR (RT/PCR). Results: The overall seroprevalence was 35%, with 40.8% in sheep and 28.4% in goats out of 945 sera that were tested. In the River Nile State, the prevalence was 30.1% (34.4% in sheep, and 24.6% in goats). In Northern State, it was 41.8% (50.5% in sheep, 33% in goats). Using IcELISA, the overall PPRV antigen detected in these two states of Northern Sudan was 7.7%; in River Nile State, it was 5% in sheep. In Northern State, 15.4% of sheep and 20% of goat lung tissue samples tested positive. PPR genome could be detected by RT/PCR. Conclusion: The results pointed to the increased prevalence of the disease in Northern Sudan, especially the Northern State. J. Adv. Vet. Anim. Res., 12(2): 327–333, June 2025 http://doi.org/10.5455/javar.2025.l900